2 - Les Travaux de Recherche sur l’UMOA: Un Aperçu - Abdoulaye Dia (Africa Development, 1991)
Having reviewed the extant literature on the Franc Zone and the West African Monetary Union (WAMU) and based on an analysis of the rolet function and various policies cf the Central Bank of West African States (BCEAO), the author predicts the emergence of an intensified research interest on WAMU. Earlier studies had concluded that the benefits that WAMU members have enjoyed from this Union in the years between 1960-1970 had for the most part been transformed to costs in the 1980s. Is it possible to dissociate the benefits from their membership in WAMU from that which results from this membership in the Franc Zone. More importantly will this Union be able to adopt and survive within the context of the new global economy? Such a research problématique is imperative in light of three conjunctural factors ; the Construction of European Monetary Union with its implications for the Franc Zone; the growing competition from the industrial and agricultural products of Nigeria and its impact on the rate of exchange between the naira and CFA Franc; the lack of adoptability of the productive structures of countries in WAMU to world demand and to internal consumption.